2006
DOI: 10.1242/dev.02429
|View full text |Cite
|
Sign up to set email alerts
|

Thebrain tumorgene negatively regulates neural progenitor cell proliferation in the larval central brain ofDrosophila

Abstract: Brain development in Drosophila is characterized by two neurogenic periods, one during embryogenesis and a second during larval life. Although much is known about embryonic neurogenesis, little is known about the genetic control of postembryonic brain development. Here we use mosaic analysis with a repressible cell marker (MARCM) to study the role of the brain tumor (brat) gene in neural proliferation control and tumour suppression in postembryonic brain development of Drosophila. Our findings indicate that ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
293
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(312 citation statements)
references
References 40 publications
14
293
0
5
Order By: Relevance
“…Prospero, which encodes a homeodomain transcription factor associated with the differentiation of ganglion mother cells after asymmetric stem cell division of neuroblasts in the central brain [42,43], is the only target gene that has been found to be directly regulated by Tll in postembryonic stages [44]. In the mouse, multiple genes involved in the development of the CNS and visual system have been identified as Tlx targets, such as Gsh2, Pax2, Pten, p21, p57, S100b, Aqp4, Plce1, Wnt7a, microRNA-9, Bmp4, and GFAP [21,[32][33][34][35][36][37][45][46][47][48][49][50] (Table 1).…”
Section: Tlx Expression Its Targets and Related Signal Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospero, which encodes a homeodomain transcription factor associated with the differentiation of ganglion mother cells after asymmetric stem cell division of neuroblasts in the central brain [42,43], is the only target gene that has been found to be directly regulated by Tll in postembryonic stages [44]. In the mouse, multiple genes involved in the development of the CNS and visual system have been identified as Tlx targets, such as Gsh2, Pax2, Pten, p21, p57, S100b, Aqp4, Plce1, Wnt7a, microRNA-9, Bmp4, and GFAP [21,[32][33][34][35][36][37][45][46][47][48][49][50] (Table 1).…”
Section: Tlx Expression Its Targets and Related Signal Pathwaysmentioning
confidence: 99%
“…Appropriate tll expression is crucial for the suppression of prospero expression and maintenance of the proliferation capacity in neuroblasts. In contrast, in the ganglion mother cells derived from neuroblasts through asymmetric division, a lack of tll expression and elevated prospero expression promote differentiation [42,43]. It has been reported that ectopic expression of tll in ganglion mother cells inhibits apoptosis, promotes cell-cycle progression, and results in tumor formation in the Drosophila brain [44].…”
Section: Roles Of Tlx Homologues In the Regulation Of Nscs And Brain mentioning
confidence: 99%
“…Cependant, quand on injecte des cellules issues du système nerveux central de mouches SAKOE dans l'abdomen de mouches sauvages, celles-ci développent des tumeurs, conséquence d'une prolifération excessive de neuroblastes [12]. C'est d'ailleurs le cas pour les mouches déficientes dans le processus de division asymétrique [30,31,34,39,40]. Cette prolifé-ration excessive est due au fait que les mouches possédant plusieurs centrosomes présentent des défauts d'orientation du fuseau mitotique et une mauvaise ségrégation des déterminants d'identité cellulaire.…”
Section: Synthèse Revuesunclassified
“…They have been shown to participate in numerous distinct processes, including roles in development, both normal and tumorous, asymmetric cell divisions and viral response (Arama et al, 2000;Horn et al, 2004;Bello et al, 2006;Betschinger et al, 2006;Lee et al, 2006;Sakuma et al, 2007) and see Table 2 in Meroni and Diez-Roux (2005), to name but a few. This protein superfamily is characterized by the presence of multiple protein-protein interaction domains, from which it has derived its name, that is, RING, B-box, and coiled-coil domains (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…BRAT, on the other hand, has been the subject of intense study in recent times (Bello et al, 2006;Betschinger et al, 2006;Lee et al, 2006) and as the name suggests, gives rise to brain tumours when mutated (Woodhouse et al, 1998;Arama et al, 2000). Tumours arising in brat animals are highly proliferative, invasive, transplantable and lethal to the animal (Woodhouse et al, 1998).…”
Section: Introductionmentioning
confidence: 99%